Editorial - Salinas Gamero, Teresa Francisca (2023)
It is with special appreciation that we write to you, on this occasion to send you the second 2023 edition of our Engineering Profiles magazine. In it, we focus on highlighting the innovations and research that are being carried out at the Faculty and other universities in the country and abroad that have collaborated with this edition. Engineering has always been a profession in constant evolution and adaptation, and in these times of rapid and challenging change, its role is more indispensable than ever. In times of crisis like those we face nationally and globally, engineers are challenged to demonstrate their ability to overcome obstacles, find creative solutions and improve people's quality of life.